L'après 2013 des confréries soufies égyptiennes : allégeance au pouvoir, dissensions internes et « renouveau du discours religieux ». (September 2019) - Paonessa, Costantino
This article discusses the role of some Sufi orders and some of their sheikhs who are members of the Higher Council of Egyptian Sufi Brotherhoods in the project to 'renew religious discourse' (tajdīd khitab al-dīnī) launched by President al-Sissi in 2015. In particular, it raises the question of the extent to which contemporary Sufi ulemas reclaim concepts belonging to the Islamic mystical tradition, such as that of tajdīd (renewal), in order to adapt it to the needs of the country's political agenda. Finally, based on the case of the al-'Azamiya brotherhood, this article aims to question the role played by Sufi identity as a factor of political mobilisation.